AN IMPROVED WHITE CELL DILUENT FOR USE WITH THE EEL ELECTRONIC BLOOD CELL COUNTER. Issue 3 (May 1960) - Taylor, F.; Rickards, A. G.
Abstract : An improved white cell diluent for use with the Eel electronic counter is described. It possesses advantages over previously described diluents in the rapidity of its action as a red cell stromalysin and in its ability to conserve surviving leucocytes for long periods of time. These properties enable counts to be made either immediately after preparation of the suspension or several hours later. The diluent is equally suitable for use with capillary or venous blood samples. When used for counting leucocytes it has been found necessary to effect a minor modification to the machine whereby the light intensity is reduced by approximately one-half.